Phase relations in the system Cu-Fe-Ni-S and their application to the slow cooling of PGE matte - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2006.